Saccades Influence the Visibility of Targets in Rapid Stimulus Sequences: The Roles of Mislocalization, Retinal Distance and Remapping - Fracasso, Alessio; Melcher, David (Frontiers in Systems Neuroscience, 2016)
Briefly presented targets around the time of a saccade are mislocalized towards the saccadic landing point. This has been taken as evidence for a remapping mechanism that accompanies each eye movement, helping maintain visual stability across large retinal shifts. Previous studies have shown that spatial mislocalization is greatly diminished when trains of brief stimuli are presented at a high frequency rate, which might help to explain why mislocalization is rarely perceived in everyday viewing. Studies in the laboratory have shown that mislocalization can reduce metacontrast masking by causing target stimuli in a masking sequence to be perceived as shifted in space towards the saccadic target and thus more easily discriminated. We investigated the influence of saccades on target discrimination when target and masks were presented in a rapid serial visual presentation (RSVP), as well as with forward masking and with backward masking. In a series of experiments, we found that performance was influenced by the retinal displacement caused by the saccade itself but that an additional component of un-masking occurred even when the retinal location of target and mask was matched. These results speak in favor of a remapping mechanism that begins before the eyes start moving and continues well beyond saccadic termination.